Origin story : the trials of Charles Darwin - Markel, Howard (W. W. Norton & Company, 2024)
"By early morning of June 30, 1860, a large crowd began to congregate in front of Oxford University's brand-new Museum of Natural History. The occasion was the annual meeting of the British Association for the Advancement of Science, and the subject of discussion was Charles Darwin's new treatise: fact or fiction? Darwin, a simultaneously reclusive and intellectually audacious squire from Kent, claimed to have solved 'that mystery of mysteries,' introducing a logical explanation of the origin of species--how they adapted, even transmogrified, through natural selection. At stake, on that summer's day of spirited debate, was the very foundation of modern biology, not to mention the future of the church. Without fear of exaggeration, Darwin's thesis would forever change our understanding of the life sciences and the natural world. And yet the author himself was nowhere to be found in the debate hall--instead, he was miles away, seeking respite from a spate of illnesses that had plagued him for much of his adult life. In Origin Story, medical historian Howard Markel recounts the two-year period (1858 to 1860) of Darwin's writing of On the Origin of Species through its spectacular success and controversy. Simultaneously, Markel delves into the mysterious health symptoms Darwin developed, combing the literature to emerge with a cogent diagnosis of a case that has long fascinated medical historians. The result is a colorful portrait of the main, his friends and enemies, and his seminal work, which resonates to this day"--